The influence of raw material growth region, anatomical structure and chemical composition of wood on the quality properties of particleboards - Bardak, Selahattin; Nemli, Gökay; Tiryaki, Sebahattin (Maderas. Ciencia y Tecnología, 2017)
In the present study, the impact of raw material grown region on the physical, mechanical, surface properties and formaldehyde emission of the particleboard was investigated. Ailanthus altissima wood grown in Trabzon had longer fiber length and thicker fiber and trachea cell wall than those of the wood grown in Artvin. The highest amounts of lignin, ash, condensed tannin and solubility values were found in wood grown in Artvin. Ailanthus altissima wood grown in Trabzon had higher amounts of cellulose and hemicellulose than those of the wood grown in Artvin. Particleboards made from wood grown in Artvin had worse surface quality and mechanical strength properties than those of panels made from wood grown in Trabzon. On the other hand, the results showed that particleboards produced from wood grown in Artvin had lower thickness swelling and formaldehyde emision values than those of the panels produced from wood grown in Trabzon.